2015
DOI: 10.1002/14651858.cd011584.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximeters to self monitor oxygen saturation levels as part of a personalised asthma action plan for people with asthma

Abstract: We found no reliable data to support or refute patient use of pulse oximeters to monitor oxygen saturation levels when experiencing an asthma attack. People should not use a pulse oximeter without seeking advice from a qualified healthcare professional.We identified no compelling rationale for home monitoring of oxygen levels in isolation for most people with asthma. Some people have a reduced perception of the severity of their own breathlessness when exposed to hypoxia. If trials on self monitoring of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…One systematic review was found, which revealed no evidence to support or refute the added value of pulse oximeters to self-monitor oxygen saturation levels as part of home monitoring using a personalized asthma action plan, since the systematic search yielded zero randomized controlled trial studies [ 149 ].…”
Section: Resultsmentioning
confidence: 99%
“…One systematic review was found, which revealed no evidence to support or refute the added value of pulse oximeters to self-monitor oxygen saturation levels as part of home monitoring using a personalized asthma action plan, since the systematic search yielded zero randomized controlled trial studies [ 149 ].…”
Section: Resultsmentioning
confidence: 99%
“…[66,67,78,79,68,[71][72][73][74][75][76][77] Similarly, while it seems intuitive that the enormous expansion in technology, such as apps on smartphones, to support self-management would be beneficial, again the evidence is decidedly limited. [72,80,81] There are some areas where it has been shown to be helpful, such as control of oral anti-coagulation, [82] this does not seem to be the case with others, such as pulse oximetry, [83] at least with existing technology and user skills.…”
Section: Task Shifting To Patientsmentioning
confidence: 99%
“…These oximeters also allow clinicians to monitor SpO2 in many settings outside of the acute care hospital. Likewise, use of inexpensive fingertip oximeters may become an important tool in patient self-management of chronic diseases if they provide consistent, accurate measurements [10].…”
mentioning
confidence: 99%